2020
DOI: 10.1101/2020.11.16.383877
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Temperature heterogeneity correlates with intraspecific variation in physiological flexibility in a small endotherm

Abstract: Phenotypic flexibility allows individuals to reversibly modify trait values and theory predicts an individual’s relative degree of flexibility positively correlates with the environmental heterogeneity it experiences. We tested this prediction by integrating surveys of population genetic and physiological variation with thermal acclimation experiments and indices of environmental heterogeneity in the Dark-eyed Junco (Junco hyemalis) and its congeners. We combined measures of thermogenic capacity for ~300 indiv… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 92 publications
(119 reference statements)
2
5
0
Order By: Relevance
“…In the brain, heat exposure influenced genes regulating synaptic activity, whereas cold exposure influenced genes involved in cellular stress response, such as protein folding. Finding hot‐ and cold‐specific responses aligns with studies across a range of taxonomic groups suggesting that high and low temperatures are distinct stressors (Bellis & Denver, 2017; Sonna et al, 2002), and that variability in temperature may represent yet another selective pressure (Sheldon, 2019; Stager et al, 2021). We also found that fewer genes were differentially expressed in the cold–TNZ contrast as compared to the hot–TNZ contrast, for both the brain and the gonad, suggesting that high temperatures may impact transcriptomic responses to a greater degree than low temperatures.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…In the brain, heat exposure influenced genes regulating synaptic activity, whereas cold exposure influenced genes involved in cellular stress response, such as protein folding. Finding hot‐ and cold‐specific responses aligns with studies across a range of taxonomic groups suggesting that high and low temperatures are distinct stressors (Bellis & Denver, 2017; Sonna et al, 2002), and that variability in temperature may represent yet another selective pressure (Sheldon, 2019; Stager et al, 2021). We also found that fewer genes were differentially expressed in the cold–TNZ contrast as compared to the hot–TNZ contrast, for both the brain and the gonad, suggesting that high temperatures may impact transcriptomic responses to a greater degree than low temperatures.…”
Section: Discussionsupporting
confidence: 72%
“…In the brain, heat exposure influenced genes regulating synaptic activity, whereas cold exposure influenced genes involved in cellular stress response, such as protein folding. Finding hot-and cold-specific responses aligns with studies across a range of taxonomic groups suggesting that high and low temperatures are distinct stressors (Bellis & Denver, 2017;Sonna et al, 2002), and that variability in temperature may represent yet another selective pressure (Sheldon, 2019;Stager et al, 2021).…”
Section: Thermal Challenges: Distinct and Shared Responses To High An...supporting
confidence: 75%
“…For each individual, we quantified resting metabolic rate (the minimum oxygen consumption at rest, in the dark) and summit metabolic rate (the maximum oxygen consumption under cold exposure) using open-flow respirometry. Summit metabolic rate data have been previously published (Stager et al 2021). Birds were not fasted before either measurement.…”
Section: Methodsmentioning
confidence: 99%
“…Previous research on vertebrates has focused on mean temperatures, rather than examining tolerance to shifts between high and low temperatures (4)(5)(6)(7)(8)(9)(10)(11). While it is clearly important to investigate the effect of mean temperatures, whether populations persist in the face of climate change depends on whether reproductive success is maintained during temperature fluctuations (12)(13)(14)(15)(16)(17)(18)(19).…”
Section: Main Textmentioning
confidence: 99%